2017
DOI: 10.5812/jhealthscope.63210
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Determinants of Catastrophic Health Expenditures in Iran: A Systematic Review and Meta-Analysis

Abstract: Objective: In this systematic review, we aimed at estimating the pooled prevalence of catastrophic health expenditures (CHE) in Iran and identifying and summarizing the determinants of CHE among Iranian households. Methods:We comprehensively searched the literature on November 2016 in PubMed, Scopus, Web of Science, the Cochrane Library, and 3 Persian databases. We also obtained the literature through colleague communications. Two review authors independently selected studies, extracted data, and evaluated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 14 publications
1
35
1
Order By: Relevance
“…At 40% of capacity to pay, 6.6% to 63.6% of Nigerian households incurred financial catastrophe while accessing health care. In contrast, similar reviews have found that smaller proportions of households experienced CHE at this same threshold . Similarly, a study conducted using the Kenya Household Health Expenditures and Utilization Survey data of 2007 found that 11.7% of households experienced catastrophic expenditures and 4% were impoverished by health care payments .…”
Section: Discussionmentioning
confidence: 94%
“…At 40% of capacity to pay, 6.6% to 63.6% of Nigerian households incurred financial catastrophe while accessing health care. In contrast, similar reviews have found that smaller proportions of households experienced CHE at this same threshold . Similarly, a study conducted using the Kenya Household Health Expenditures and Utilization Survey data of 2007 found that 11.7% of households experienced catastrophic expenditures and 4% were impoverished by health care payments .…”
Section: Discussionmentioning
confidence: 94%
“…Identifying the imposed financial risk on diabetic patients due to health-care costs and the other related factors can lead to more effective efforts to alleviate this problem. 11 Many studies have been conducted on health-care expenditures and have examined the incidence of CHE among households in Iran 17,[22][23][24] but no studies have been done so far among the diabetics on the index of CHE which causes poverty. A study by Rezaei and Hajizadeh 25 showed that 5.26% of Iranian households faced CHE in 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the emphasis placed on health financial support provision for people with disability and the elderly, yet disability and aging are identified as risk factors for dealing with catastrophic health expenditures in the upstream documents . Evidence shows that there is no specific strategy to support people with disability to have access to healthcare services and health insurance beyond the basic coverage .…”
Section: Discussionmentioning
confidence: 99%
“…Despite the emphasis placed on health financial support provision for people with disability and the elderly, yet disability and aging are identified as risk factors for dealing with catastrophic health expenditures in the upstream documents. 33 Evidence shows that there is no specific strategy to support people with disability to have access to healthcare services and health insurance beyond the basic coverage. 34 Therefore, the development of targeted policies to guarantee the full coverage of these groups and effective institutional coherence will be a key step toward achieving ideal financial supports for such vulnerable groups.…”
Section: Discussionmentioning
confidence: 99%